2021
DOI: 10.1007/s11250-021-02674-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding olive cake silage up to 20% of DM intake in sheep improves lipid quality and health-related indices of milk and ovine halloumi cheese

Abstract: This study aimed to evaluate the use of a by-product, olive cake silage (OCS), as a forage replacement in sheep diets for the improvement of fatty acid (FA) content of milk and thus, the lipids of the ovine halloumi cheese produced. Sixty second-parity purebred Chios ewes in mid-lactation were assigned to three diet treatments (2 lots of 10 animals per treatment) receiving 0%, 10%, and 20% of OCS on dry matter basis for 3 weeks (treatments S0, S10, and S20, respectively). Halloumi cheese was manufactured from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
7
2
Order By: Relevance
“…It has been reported that heating, the fermentation culture used, and the ripening time required for the production of cheese could potentially modulate cheese FA composition [4]. However, in our previous studies [28,54], the FA profiles of milk and related Halloumi cheese produced were similar, which suggested that the improvement in nutritional quality achieved in milk due to organic practices is possibly further maintained in organic Halloumi cheese in the present study.…”
Section: Effect Of Farming System and Season On Fa Profile Of Halloumi Cheesecontrasting
confidence: 57%
“…It has been reported that heating, the fermentation culture used, and the ripening time required for the production of cheese could potentially modulate cheese FA composition [4]. However, in our previous studies [28,54], the FA profiles of milk and related Halloumi cheese produced were similar, which suggested that the improvement in nutritional quality achieved in milk due to organic practices is possibly further maintained in organic Halloumi cheese in the present study.…”
Section: Effect Of Farming System and Season On Fa Profile Of Halloumi Cheesecontrasting
confidence: 57%
“…Several ruminants (Yáñez- Ruiz and Molina-Alcaide, 2007;Awawdeh, 2011;Abbeddou et al, 2011a,b;Estaún et al, 2014;Castellani et al, 2017;Kotsampasi et al, 2017;Awawdeh et al, 2020;Neofytou et al, 2020;Alkhtib et al, 2021;Symeou et al, 2021;Tzamaloukas et al, 2021) and monogastric meat species (Rupić et al, 1999;Paiva-Martins et al, 2014;Parsaei et al, 2014;Ait-Kaki et al, 2018;Reda et al, 2020) have been investigated, but beef cattle appear to be under-represented. Moreover, most of the studies mainly focus on animal performance and/or the final product or the rumen function (Estaún et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The forage substitution with ensiled OC in the diets of dairy cows for a short-term period, in our study, had a marked effect on milk FA composition by increasing the content of total MUFA and reducing the levels of saturated FA, particularly MCFA. Previously, studies in cows (Castellani et al 2017;Neofytou et al 2020), ewes (Chiofalo et al 2004;Abbeddou et al 2011aAbbeddou et al , b, 2015Symeou et al 2019Symeou et al , 2021, and goats (Molina-Alcaide et al 2010) reported a linear decline in SFA content with concomitant increased levels of MUFA by supplemented diets with various forms of processed OC. It is likely that MUFA of feed, escaping rumen biohydrogenation (BH), were transferred to milk FA content through mammary uptake from the plasma dietary FA, contributing to the higher MUFA content of milk (Shingfield et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, OC may improve the lipids of milk due to its richness in oleic acid. Studies performed in dairy sheep demonstrated a decrease in saturated fatty acids (SFA) and an increase in monounsaturated FA (MUFA) and, in some cases, increased specific beneficial UFA, such as conjugated linoleic acid (CLA), content of milk by the inclusion of dried (Abbeddou et al 2011a(Abbeddou et al , b, 2015, partly destoned fresh (Chiofalo et al 2004) or ensiled OC (Symeou et al 2019(Symeou et al , 2021. Recent studies in dairy cows reported similar results.…”
Section: Introductionmentioning
confidence: 85%